Investigation of the effects of some antibiotics and vitamin A on the polymorphonuclear leucocyte functions of neurotropenic children - BEKİROĞLU, GÜLNAZ NURAL (My University, 2007)
In this study the in vitro effects of imipenem, cefodizime, vancomycin, teicoplanin, imipenemamikacin, imipenem-teicoplanin combinations and vitamin A at therapeutic concentration on phagocytic and intracellular killing activity of polymorphonuclear leukocytes (PMNs) in neutropenic children with acute leukemia were investigated. Twenty-one neutropenic children with mean age 7 were included in this study and were clinically divided in 3 groups. The first group included 7 nonfebrile neutropenic children not receiving chemotherapy; the second group included 7 febrile neutropenic children receiving chemotherapy; the third group included 7 nonfebrile neutropenic children receiving chemotherapy. PMNs were isolated by Ficoll-Hypaque gradient centrifugation method. C. albicans ATCC 10231 was used to measure the phagocytosis and intracellular killing activity of PMNs. Consequently, in the 1st group; the antibiotics used in our investigation and vitamin A significantly increased PMN’s phagocytic activity, cefodizime showed immunomodulatory effect on the both PMN functions in the 1st and 2st group. Additionally, vancomycin had immunomodulatory effect on the both PMN functions in the 1st group and only on the phagocytic activity in 3rd group.

Bu çalışmada terapötik konsantrasyonlardaki imipenem, sefodizim, vankomisin, teikoplanin ile imipenem-amikasin, imipenem-teikoplanin kombinasyonlarının ve A vitamininin akut lösemili nötropenik çocuk hastalarda, polimorf nüveli lökositlerin (PNL) fagositik ve hücre içi öldürme aktivitesi üzerine etkisi in vitro olarak araştırılmıştır. Yaş ortalaması 7 olan 21 nötropenik çocuk hasta, klinik olarak 3 gruba ayrılarak çalışmaya dahil edilmiştir. Birinci grupta kemoterapi almayan nonfebril nötropenik 7 çocuk, ikinci grupta kemoterapi alan febril nötropenik 7 çocuk ve üçüncü grupta kemoterapi alan nonfebril nötropenik 7 çocuk yer almıştır. PNL’ler Ficoll-Hypaque gradient santrifüjleme yöntemi ile izole edilmiştir. Fagasitoz ve hücre içi öldürme aktivitesinin tayininde C. albicans ATCC 10231 suşu kullanılmıştır. Sonuç olarak, çalışmamızda kullanılan antibiyotikler ve A vitamini 1. grupta PNL’lerin fagositik aktivitesini artırmıştır. Sefodizim 1. ve 2. grupta her iki PNL fonksiyonu üzerine immünomodülatör etki göstermiştir. Buna ilaveten vankomisin 1. grupta her iki PNL fonksiyonu ve 3. grupta fagositik aktivite üzerine immünomodülatör etki göstermiştir.
Nötropenik çocukların polimorf nüveli lökosit fonksiyonları üzerine bazı antibiyotiklerin ve A vitamininin etkisinin araştırılması
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Eczacılık; Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Pharmacology and Therapeutics; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; TIBBİ BİLİŞİM; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; MEDICAL INFORMATICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Yaşam Bilimleri; General Health Professions; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; Life Sciences; Polymorphonuclear leukocyte; phagocytosis; intracellular killing; neutropenia; antibiotic; vitamin A; Polimorf nüveli lökosit; fagositoz; hücre içi öldürme; nötropeni; antibiyotik